MODEL PEMBELAJARAN INQUIRI DALAM UPAYA MENINGKATKAN HASIL BELAJAR EKONOMI SISWA - Nanda Yanti Sitanggang (PUSKAPAD, 2022)
This research is a class action research (class action research). This research was conducted at SMA Negeri 1 Kota Pinang with the number of research subjects as many as 43 students consisting of one class. The results of observing student activities have been motivated to carry out the activities contained in the inquiry model learning. Student activity in each cycle increased by 11.51%, in the first cycle 51.16% while in the second cycle 79.06%, it can be concluded that the student's ability has been categorized as high. The application of the inquiry model succeeded in increasing student learning outcomes, it can be seen from the changes in student learning outcomes, in the first cycle the average student was 51.16, while in the second cycle the average value was 79.06. The increase in the average value of students from cycle I to cycle II is 11.51 students who achieve the standard of graduation according to the school's KKM is a value of 70, so it can be concluded, student learning outcomes are declared complete.